GENETIC ANALYSIS OF SOME QUALITATIVE TRAITS IN PEA (PISUM SATIVUM L.) FOR F4 GENERATION IMPLEMENTED BY HALF DIALLEL DESIGN SYSTEM. - Suaad Muhammad Sheikh Abdulla, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was carried out, to estimate some chemical components of fifteen genotypes of pea (Pisum sativum L.) (five parents+ ten crosses) produced using half diallel crossing system implemented by Randomized Complete Block Design (RCBD), repeated three times. The Least Significant Difference test (LSD) at 0.01 significant levels was used to compare means. The following is a summary of the study's findings:The mean squares of genotypes, GCA and SCA were highly significant for all studied traits except GCA mean squares of protein which was only significant. The cross (Avolla× Jeza) showed maximum protein and oil% reached 18.613 and 1.287% respectively, while maximum starch% was 58.403% showed by the cross (America× Jeza). Parent (America) showed the best performance for protein, oil and fiber% which recorded 19.793, 1.737 and 1.577% respectively. The cross (Avolla× Jeza) showed the best value for heterosis and heterobeltosis due to protein%, while the cross (America× Jeza) gave the highest values for heterosis and heterobeltosis for starch. The magnitude of  was larger than  for all studied traits confirming the importance of non-additive gene effect in controlling the inheritance of these traits. Heritability in broad sense was found to be high for all traits, while it was moderate for protein and ash and low for the other traits.